2020
DOI: 10.3390/jcm9123923
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Glutamate-Pyruvate Transaminase, Glutamate-Oxaloacetate Transaminase and Gamma-Glutamyl Transferase in 1494 Patients with Various Genotypes for the Alpha-1 Antitrypsin Gene

Abstract: Background: Patients with liver disease associated with alpha-1 antitrypsin deficiency (AATD) are homozygous for the Z mutation, leading to chronic liver damage. Objective: To assess the serum levels of glutamate-oxaloacetate transaminase (GOT), glutamate-pyruvate transaminase (GPT), and gamma-glutamyl transpeptidase (GGT) in patients with different genotypes for the alpha-1 antitrypsin (AAT) gene. Methods: Patients (n = 1494) underwent genotyping of the SERPINA1 gene, together with a determination of AAT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Liver enzymes have often been used to screen liver disease in AATD in clinical practice [ 36 ]. In our cohort, elevated liver enzymes and FIB-4 were more frequently observed in patients with LSM > 7.5 kPa, but normal levels were also frequently present in patients with high LSM.…”
Section: Discussionmentioning
confidence: 99%
“…Liver enzymes have often been used to screen liver disease in AATD in clinical practice [ 36 ]. In our cohort, elevated liver enzymes and FIB-4 were more frequently observed in patients with LSM > 7.5 kPa, but normal levels were also frequently present in patients with high LSM.…”
Section: Discussionmentioning
confidence: 99%
“…A bibliographic search was carried out in MEDLINE, Embase (through Ovid), and Google Scholar, until December 2023, looking for studies on prevalence of AATD in the general population and in screening of people clinically suspected of being affected by AATD in Macaronesia, selecting studies published in journals reviewed by peers in order to create a database with reliable results. With the keywords "Alpha-1 antitrypsin deficiency" and the name of each archipelago, in English, and some articles cited in the bibliography of those selected, 16 articles were compiled: 2 on Madeira [7,8], 13 on the Canary Islands [9][10][11][12][13][14][15][16][17][18][19][20][21], and 1 on Cape Verde [22]. None was found about the Azores.…”
Section: Methodsmentioning
confidence: 99%
“…Hernandez-Perez et al demonstrated that the presence of a PI*Z allele seemed to be a risk factor for developing hepatic damage. Deficient AAT genotypes were linked to changes in liver enzymes, and low AAT levels were associated with high liver enzyme levels [15]. Pons et al showed that abnormal liver enzymes are common in patients with AATD; however, most patients do not have significant liver fibrosis.…”
mentioning
confidence: 99%